O uso das Tecnologias da Informação e Comunicação (TICs) no ensino de genética mendeliana em um ensino remoto - Oliveira, Arleane Silva (Brasil, 2021)
This study aimed to develop a teaching-learning experience, focusing on ICTs in Biology classes in Mendelian Genetics content. The research was based on the qualitative-quantitative research approach in education. The project was carried out in two state public schools located in the municipality of Itacoatiara-AM. Of the 123 students enrolled in the 3rd grade of high school, 53 students participated in this study. The methodology consisted of 3 steps: Step I- survey for prior knowledge; a pre-test quiz; Stage II-Video projection; interactive game play and a post-test quiz; Stage III-Questionnaire for evaluating the developed methodology. The application of the game resulted in 58% of correct answers in the questions. In the post-test, after performing the didactic sequence of stage II, the average yield of correct questions was 65%, compared to 46% in the pre-test. Although the students had the problem related to the limitation of the internet, the proposal carried out had a satisfactory rate of effectiveness.